Les déterminants de la réduction de la fracture numérique à Madagascar - Alexandra Razafindrabe (Netcom)
The issue of the digital divide is recurrent in the literature on information and communication technologies and in the economic literature. Madagascar, the Big Island of the Indian Ocean, is one of those territories with an undeniable development potential but which is unable to overcome its economic difficulties. ICTs could be a bridge for the country's development, but only if they manage to play their role as a lever for development. We examine the elements linked to the reduction of the digital divide in Madagascar and note that the variables linked to the degree of the use of new information and communication technologies are the level of education, geographical location and belonging to a religious network.